Interactive Edutainment Game: Learning Media for Integer Operations for Middle School Students - Aryanti, letty; Aryasandy, Nensy; Yerizon, Yerizon (Insitut Agama Islam Negeri Kerinci, 2024)
This study aims to develop and evaluate the effectiveness of an HTML5-based interactive learning media in the form of an edutainment game to enhance Junior High School (JHS) students' understanding of integer arithmetic operations. Adopting a Research and Development (R&D) approach, the media was developed through seven stages of the Borg and Gall model: needs analysis, planning, product development, expert validation, initial product revision, field testing, and final product revision. The research subjects consisted of 30 seventh-grade students, one mathematics teacher, and three expert validators. The validation results indicated that the media was